Combining XRD and SEM techniques with site selective spectroscopy for structural and spectroscopic studies of Nd3+-doped LuPO4 micro-powders. Issue 16 (November 2020) - Prokop, K.A.; Guzik, M.; Guyot, Y.; Boulon, G.; Cybińska, J.
Abstract: We present and discuss the structural and spectroscopic properties of micro-crystalline Nd 3+ -doped LuPO4 zircon-(xenotime)-type orthophosphates (0.5–20 mol% of Nd 3+ ions) synthesized by high-temperature solid-state reaction, in which Nd 3+ optical rare earth ion plays the role of a structural probe. Surprisingly, in the literature there are not many studies performed for this optical material. The basic structural research with detailed information about the non-equivalent symmetry sites for the powdered samples with different Nd 3+ ion concentrations is still missing. It is very important to fulfill this gap in order to properly apply this optical material. A series of Nd 3+ -doped LuPO4 micro-powders were obtained by using molar ratio of Lu2 O3, Nd2 O3, and NH4 H2 PO4 as the starting materials. Also, for some samples the 10% of ammonium dihydrogen phosphate excess was applied. The XRD and SEM analysis reveal some dependence of Nd 3+ ion concentration and synthesis route on the crystal structure. The low-temperature high-resolution techniques like absorption spectroscopy at 4.2 K and site-selective tuneable laser spectroscopy at 77 K allowed to take advantage of Nd 3+ ion as a probe for local ordering due to the close relation between its spectroscopic properties and the local structure at the ion site. To the best of our knowledge such a study has not been reported for micro-powdered Nd 3+ -doped LuPO4 .